Implementation of the National Policy Framework on Public Participation in the Ugu district municipality - Ngwane, Ntombenhle Precious (My University, 2017)
Successfully translating policy intentions to desired policy outputs has been identified as a challenge that most developing countries and emerging democracies are faced with. In the early 1970s theorists and researchers realised that in part the problem is not paying enough attention to policy implementation. As a result, more research effort was put into understanding policy implementation and what factors contribute towards or impede a successful implementation of policies. This research is aimed at exploring the factors that contribute to successful implementation of policies in South African Local Government. Focus has been put on institutional provisions that are put in place by these local government institutions to support the implementation of policies. The policy used for the purposes of this study is the National Policy Framework on Public Participation (NPFPP) and the area of focus is the Ugu District. The study followed the qualitative method and nineteen (19) in-depth interviews were held with members of government, civil society and community members and representatives. Municipal documents were analysed for purposes of validating information received from interviews. The study found that there are structural and systemic challenges that contribute to low levels of success in implementing the NPFPP in the Ugu district. This is mainly due to the fact that there are inadequate and ineffective provisions for public participation in the district. Issues identified include lack of capacity within municipalities, both in terms of understanding policy requirements and the number of staff available to implement the policy. Furthermore, there was no perceived involvement of all the strategic units within the municipality to implement the policy. The external structures put in place by the municipalities in accordance with the provisions of the policy, that is, ward committees and IDP processes, proved inadequate and ineffective. The study also found that communities were unaware of their right and responsibility to participate in municipal matters. However, willingness and eagerness to work with the municipalities was displayed by both communities and civil society organizations. The study concluded by making recommendations for implementation of the NPFPP in local government generally and also recommendations for the specific area of interest.
A research report submitted to the Faculty of Management, University of Witwatersrand, in 50% fulfilment of the requirements for the degree of Masters of Management in the field of Public Policy June 2017
Keywords: Political participation--South Africa--KwaZulu-Natal; Civil society--South Africa--KwaZulu-Natal; Local government--South Africa--Citizen participation